Analisis Variasi Bentuk Karapaks Kuya Batok (Cuora amboinensis Daudin, 1802) dan Bajuku (Orlitia borneensis Gray, 1873) dengan Metode Elliptic Fourier Descriptors - Tony Febri Qurniawan; Dina Rusiana; Abdul Rachman (Fakultas Biologi | Universitas Jenderal Soedirman, 2011)
Turtles is easily identified because of its shield. The dorsal shield or commonly called carapace is one of characteristics that can be used for turtle’s identification. People and researchers usually can distinguish the turtles just by looking at the carapace valve, but not in carapace shape. Both of them sometimes have their own interpretation about it, because carapace shape has a variation. This research was aimed to obtain some information about differences of carapace shape variation between Coura amboinensis and Orlitia borneensis quantitatively and also to investigate about characteristic of variation on carapace shape of a species. The specimens were taken from Pusat Penyelamatan Satwa Jogja. The picture of carapace shape of the turtles was changed into bitmap then processed used SHAPE ver 1.3. The variation of carapace contour were extracted by image processing, described and analyzed by Elliptic Fourier Descriptors. Mathematically independent shape characteristics were then indentified by Principal Component Analysis of The Elliptic Fourier Descriptors. Principal components represented the aspect ratio of the broad size, length size, and curve or roundness margin of the carapace. Based on result showed that intraspecies variation shape of carapace on C. amboinensis and on O. borneensis can be analysis into 3 principal component. The principal component 1st (PC1), 2nd (PC2) and 3rd (PC3) components accounted for 82.77%, 10.3% and 4.73% of total shape variation on C. amboinensis. The 1st, 2nd and 3rd components accounted for 88.1%, 7.02% and 3.71% of total shape variation on O. borneensis. The contribution ratio of PC1 was over 80% on both of species, showing that most of the variation on carapace shape could be explained by the aspect ratio. The PC2 and PC3 were less than 20%, indicated that there is small asymmetric variation degree of roundness on carapace.